Analysis of teachers’ pedagogical competence in improving the quality of learning - Amin, M; Afrianto, Fajar; Hadi, Abdul; Jaya, Indra; Aprihen, Roma; Ali, Muhammad; Maulana, Riski; Zuhdi, Hanif Naufal; Febrinola, Elwita; Kirara, Sindy; Afifah, Nurul; Astika, Mella; Putri, Yulia (Indonesian Research Journal in Education |IRJE|, 2025)
This research aimed to assess the educational abilities of teachers in terms of planning learning activities, implementing the teaching process, and making efforts to increase student motivation in learning. The research employed a qualitative approach to gather data through interviews, observations, and document collection. The data analysis process encompassed information reduction, data presentation, and conclusion. The subjects who became informants were the principal, his deputy, and educators. The results indicate that educators’ pedagogical expertise in compiling learning activities is evident in their preparation of the lesson plan. However, several teachers often do not bring it, so the learning objectives are not achieved optimally. When learning, teachers demonstrate an understanding of the material by studying the textbook’s contents. However, problems still exist in class management, and there is a lack of discipline regarding time usage. To increase students' enthusiasm for learning, teachers create opportunities for active participation by utilizing information and communication technology, establishing effective communication with them, and conducting reflection to enhance the quality of learning.